Discovery and structure activity relationships of 2-pyrazolines derived from chalcones from a pest management perspective - KAYMAKÇIOĞLU, BEDİA (SPRINGER BIRKHAUSER, 2015)
Synthesis of chalcones and 2-pyrazoline derivatives has been an active field of research due to the established pharmacological effects of these compounds. In this study, a series of chalcone (1a-i), 2-pyrazoline-1-carbothioamides (2a-i), and 2-pyrazoline-1-carboxamide derivatives (3a-g) were synthesized and screened for their potential pesticide activities. The proposed structures of all the synthesized compounds were confirmed using the elemental analysis, UV, IR, H-1-NMR, and mass spectroscopy. Among the total of 25 tested compounds, compounds 1g and 2a and 2e with Biting Deterrence Index (BDI) values of 0.85, 0.83, and 0.8, respectively, at 25 nmol/cm(2) showed the highest biting deterrent activity against Aedes aegypti, which was comparable to N,N-diethyl-3-methylbenzamide (DEET). Compounds 1g, 2a and 2e were subsequently tested in human-based repellent bioassays, and they showed MED (minimum effective dose) values of 0.375, 0.094, and 0.375 mg/cm(2), respectively. Compound 1e was the most toxic compound (LC50 = 2.58 ppm), followed by 1f (LC50 = 5.69 ppm) and 2g (LC50 = 15.14 ppm), against 1-day-old Ae. aegypti larvae. Compounds 1f and 2h 1f and 2h showed the greatest growth inhibition against Colletotrichum gloeosporioides (97.6 and 98.5 %, respectively) at the lowest dose (0.3 mu M), which was greater antifungal activity than with standard commercial fungicides captan and azoxystrobin. Compounds 2d, 2g and 2h produced 79.5, 98.3, and 82.3 % growth inhibition, respectively, at 30.0 mu M against Botrytis cinerea, which was similar to captan in the antifungal activity. The active fungicidal compounds (2d, 2g, and 2h) were weaky phytotoxic, with little or no phytotoxicity at concentrations that were fungitoxic. Compound 2h stimulated the growth of Lemma paucicostata at concentrations that are fungitoxic to several plant pathogens.
Keywords: Chalcones; 2-Pyrazolines; Carbothioamide; Carboxamide; Aedes aegypti; Colletotrichum gloeosporioides; Botrytis cinerea; Lactuca sativa; Agrostis stolonifera; Lemna paucicostata; ANTIMICROBIAL EVALUATION; BIOLOGICAL EVALUATION; PYRAZOLE; DERIVATIVES; ANTICANCER; METABOLITES